(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The essay analyzes the topic of psychosocial risks in light of evolving technologies that increasingly permeate the spaces and times of life and work, blurring their boundaries and harming the intangible dimensions of the individual. In response to the significant changes taking place in techno-capitalist society, the essay advocates for a rethinking of the relationships between individuals, work and health, emphasizing a person-centered approach. This perspective recognizes the essential and driving value of human resources for the development of businesses and the entire production system.